A critical review on polydopamine surface-modified scaffolds in musculoskeletal regeneration - Tolabi, Hamidreza; Bakhtiary, Negar; Sayadi, Shaghayegh; Tamaddon, Maryam; Ghorbani, Farnaz; Boccaccini, Aldo R.; Liu, Chaozong (Frontiers in Bioengineering and Biotechnology, 2022)
Increasing concern about age-related diseases, particularly musculoskeletal injuries and orthopedic conditions, highlights the need for strategies such as tissue engineering to address them. Surface modification has been developed to create pro-healing interfaces, personalize scaffolds and provide novel medicines. Polydopamine, a mussel-inspired adhesive polymer with highly reactive functional groups that adhere to nearly all substrates, has gained attention in surface modification strategies for biomaterials. Polydopamine was primarily developed to modify surfaces, but its effectiveness has opened up promising approaches for further applications in bioengineering as carriers and nanoparticles. This review focuses on the recent discoveries of the role of polydopamine as a surface coating material, with focus on the properties that make it suitable for tackling musculoskeletal disorders. We report the evolution of using it in research, and discuss papers involving the progress of this field. The current research on the role of polydopamine in bone, cartilage, muscle, nerve, and tendon regeneration is discussed, thus giving comprehensive overview about the function of polydopamine both in-vitro and in-vivo. Finally, the report concludes presenting the critical challenges that must be addressed for the clinical translation of this biomaterial while exploring future perspectives and research opportunities in this area.